PARCS Technology: Concept and Implementations - Anisimov, A. V.; Derevianchenko, O. V.; Kuliabko, P. P.; Fedorus, O. M. (Cybernetics and systems analysis, 2023)
An overview of PARCS (Parallel Asynchronous Recursive Control Space) technology developments is provided. The concept of the control space, i.e., a model apparatus, based on which the logical structure of the investigated problem (system) is described, and dynamic changes in it are reflected, is considered. The PARCS model is proposed whose application leads to flexible and unified adaptation to emerging programming technologies. PARCS-extension of the following programming languages is considered: PASCAL, C, FORTRAN, MODULA2, Java, CUDA, OpenCL, PYTHON, .NET, GO/PYTHON.